Chapter 3 Building local strategies for the adaptation to climate change of farming livelihoods Review of a participatory approach applied in Mesoamérica - Bouroncle, Claudia (Taylor & Francis, 2021)
There are growing technical efforts by government organizations, academics and non-government organizations to define policy frameworks to promote the adaptation of agriculture to climate change. Nevertheless, adaptation is primarily a local process; therefore, tools that link these efforts with local requirements are needed based on current and consistent information. We develop a participatory methodology to characterize and assess subsistence livelihoods vulnerability and build local strategies for adaptation to climate change based on the Community Capitals Framework and present a review of its application in five micro-watersheds of the Pacific basin of three Mesoamerican countries. We conclude that the methodology supports the rapid characterization of vulnerability based on local knowledge, showing clear differences in the current impacts of climate change, adaptive capacity and vulnerability among different livelihoods and facilitating the identification of key constraints affecting adaptation of smallholder livelihoods in each site. However, we conclude also that this methodology is still insufficient for adaptation planning because the measures proposed are focused on adjustments to the production systems, rely on external technical assistance and are not effectively connected with financing mechanisms. Based on this, we identify recommendations for the future implementation of the methodology.